Open-Air Museums in Borneo and the Dialectic of Vernacular Form - Azmah, Arzmi (Universidad De Granada, 2024)
Open-air cultural heritage museums in Borneo aim to preserve and showcase the traditional houses of the indigenous communities. However, the authenticity of these museums is questionable, as they often isolate the houses from their original context and present a romanticized view of traditional life. This paper argues that vernacular architecture in Borneo is not static but has evolved, responding to changes in socio-economic needs and globalization. The paper also highlights the indigenous people's ambivalent attitude towards traditional vernacular houses, as they represent their cultural identity but do not provide much comfort or practicality in today's world. The paper calls for open-air architecture museums in Borneo to be more inclusive, and to document the history of the indigenous people's changing lifestyles and the adaptation of their homes.